Optimization of Fluid Flushing Rate: A Study on Laboratory Drilling Setup - Rawal R.; Karmakar N.C.; Sharma S.K. (My University, 2025)
Use of the flushing media contributes to the improvement in the overall performance of drilling operations. The paper reports findings of the laboratory scale work carried out on a rotary drilling machine using sandstone rock samples. This study was conducted to develop a process to optimize the fluid flushing rate and to understand the role of drilling fluid through real-time data generation. From the laboratory experimentation, it was found that, while working with optimum flushing rate, up to 500% increment in rate of penetration (ROP) has been observed. And, also 50% reduction in ROP was noticed with the increment in depth of drilling from 3 to 12 mm. The outcome of the study convincingly demonstrates that fluid flushing rate plays a vital role in the improvement of the overall efficiency of the drilling operation of the laboratory setup. © 2022, The Institution of Engineers (India).